PMI- Agile Certified Practitioner, 3ed - Chandramouli, S.; Dutt, Saikat (Pearson India, 2016)
"This self-study guide is essential reading for all PMI-ACP aspirants to clear the certification exam. Following an easy and a step-by-step learning approach, this book presents not only the basic agile concepts but also the latest developments in the field, based entirely on the latest guidelines from the Project Management Institute."